Satisfacción y fidelización de los clientes en la tienda de abarrotes la esperanza, Requena, 2024 - Granados Mercado, Dora Susy (2024)
At the La Esperanza grocery store in Requena during the year 2024, a methodology of descriptive correlational analysis was employed using a quantitative data approach. The design was non-experimental, observing phenomena as they occur. The main results show a Cronbach's Alpha reliability coefficient of 0.889, indicating strong support for the internal consistency of the scales. The Pearson correlation between "Customer Satisfaction" and "Loyalty" is highly significant (0.970**), supporting the research hypothesis. The bilateral significance of 0.000 indicates a very significant correlation at the 0.01 level. In summary, an increase in customer satisfaction is associated with a notably higher likelihood of loyalty.